THE HOLOTYPE OF CERVALCES GALLICUS (AZZAROLI, 1952) FROM SENEZE (HAUTE LOIRE, FRANCE) WITH NOMENCLATURAL IMPLICATIONS AND TAXONOMICAL PHYLOGENETIC PROBLEMS (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2001)
The remains of Cervalces (Libralces) gallicus (Azzaroli, 1952) from the Middle-Upper Villafranchian of Sénèze (Haute-Loire, France), kept in the Paleontological Museum of the University Claude Bernard - Lyon 1, are here studied again. The remains consist of an assembled skeleton, with skull, antlers and all postcranial elements, described by Azzaroli (1952) as holotype, and in the limb bones of a second specimen, designated as cotype by the same author. The cotypeís limb bones are here attributed to the holotype, while the smaller assembled limb bones cannot be determined over the family taxonomic level, due to the bad state of preservation.The characters determining the genus Cervalces are described here and, in accordance with Azzaroli, the species C. (L.) latifrons from the Middle-Upper Pleistocene is attributed to it. All the species of the genus Cervalces show characters of cranial and facial morphology, which differ from that of present-day Alces. The narrow, deep occipital and the short nasals, not articulated with the long premaxillaris, are in this view considered apomorphic characters of Alces alces.